Innovation and international business. Issue 1 (24th November 2016) - Cantwell, John
Abstract: While classical economic theories of growth emphasised international capital accumulation, and finance-based theories of foreign investment stressed international interest rate differentials and risk reduction, the technological accumulation approach examines international knowledge building by multinational enterprises and their international business (IB) networks. The two processes of innovation and internationalisation have become ever more interconnected as central drivers of development since the first industrial revolution, through to today's information age. The increasing significance of the knowledge-seeking motive for IB networks and of competence-creating subsidiary activities at a local level have linked localised innovation systems to IB and to international knowledge exchange. From a locational perspective, international knowledge connectivity has become critical for sustained innovation and growth. The shift of techno-socio-economic paradigm in the information age is associated with a shift in the character of IB and innovation, with critical implications for IB theory and concepts.